Opioid-induced respiratory depression: reversal by non-opioid drugs - van der Schier, Rutger (Faculty of 1000 Ltd, 2014)
The human body is critically dependent on the ventilatory control system for adequate uptake of oxygen and removal of carbon dioxide (CO(2)). Potent opioid analgesics, through their actions on μ-opioid receptor (MOR) expressed on respiratory neurons in the brainstem, depress ventilation. Opioid-induced respiratory depression (OIRD) is potentially life threatening and the cause of substantial morbidity and mortality. One possible way of prevention of OIRD is by adding a respiratory stimulant to the opioid treatment, which through activation of non-opioidergic pathways will excite breathing and consequently will offset OIRD and should not affect analgesia. Various new respiratory stimulants are currently under investigation including (a) potassium channel blockers acting at the carotid bodies, and (b) ampakines and (c) serotonin receptor agonists acting within the brainstem. (a) GAL-021 targets BK(Ca)-channels. Initial animal and human experimental evidence indicates that this potassium channel blocker is a potent respiratory stimulant that reverses OIRD without affecting antinociception. GAL021 is safe and better tolerated than the older K(+)-channel blocker doxapram and more efficacious in its effect on respiration. (b) Ampakines modulate glutamatergic respiratory neurons in brainstem respiratory centers. Various ampakines have been studied showing their ability to increase respiratory drive during OIRD by increasing respiratory rate. Currently, CX717 is the most promising ampakine for use in humans as it is safe and does not affect opioid analgesia. (c) While animal studies show that serotonin receptor agonists increase respiratory drive via activation of serotonin receptors in brainstem respiratory centers, human studies are without success. Further clinical studies are required to improve our care of patients that are treated with potent opioid analgesics. The use of non-opioid adjuvants may reduce the probability of OIRD but does never relieve us of our duty to continuously monitor these patients, irrespective whether they are treated in-house or in an ambulatory setting.